OPTIMIZATION OF THE ROLE OF LEGISLATION DESIGNERS IN IMPLEMENTING HARMONIZATION OF REGIONAL REGULATION DRAFT - Iswahyudi, Fauzi; Nasution, Faisal Akbar; Suhaidi, Suhaidi (NOMOI Law Review, 2024)
Harmonization of regional regulations as an effort to ensure alignment between draft regional regulations and higher regulations. The role of the drafter of legislation is very important in this process, considering the complexity of regulations and the need for an integrated legal system. This research aims to analyze the optimization of the role of legislative regulation designers in carrying out harmonization of draft regional regulations. This research uses normative legal research with a statutory approach.. The results of the study indicate that drafters have a strategic responsibility in ensuring the consistency of legislation, both vertically and horizontally. However, a number of challenges were identified, such as lack of coordination between stakeholders, limited technical capacity, and political uncertainty that affects the independence of drafters. Effective harmonization of regional regulations requires the role of drafters who are not only legal technicians, but also facilitators in building legal integration that is responsive to the dynamics of society and the needs of regional development. This optimization is important to create regional regulations that are quality, fair, and do not conflict with higher regulations.